String solutions in Chern-Simons-Higgs model coupled to an axion - López Sarrión, J. (2006)
We study a d = 2+1 dimensional Chern-Simons gauge theory coupled to a Higgs scalar and an axion field, finding the form of the potential that allows the existence of self-dual equations and the corresponding Bogomolny bound for the energy of static configurations. We show that the same conditions allow for the N = 2 supersymmetric extension of the model, reobtaining the BPS equations from the supersymmetry requirement. Explicit electrically charged vortexlike solutions to these equations are presented.